Doing Business in the East African Community 2011 - World Bank; International Finance Corporation (World Bank, Washington, DC, 2017)
Doing business in the East African Community 2011 is a regional report that draws on the global doing business project and its database as well as the findings of doing business 2011: making a difference for entrepreneurs, the eighth in a series of annual reports investigating regulations that enhance business activity and those that constrain it. Doing business presents quantitative indicators on business regulations and the protection of property rights that can be compared across 183 economies from Afghanistan to Zimbabwe over time. This report presents a summary of doing business indicators for the East African Community. It focuses on five economies: Burundi, Kenya, Rwanda, Tanzania and Uganda. Data in doing business 2011 are current as of June 1, 2010. The indicators are used to analyze economic outcomes and identify what reforms have worked, where and why. The methodology for the employing workers indicators changed for doing business 2011.